Hydrodynamic cavitation characteristics of an orifice system and its effects on CRUD-like SiC deposition. (October 2016) - Kim, Seong Man; Bang, In Cheol
Highlights: CRUD-like SiC deposition was prepared for examining the erosion test in the cavitation field. We investigated the comparison between swirl flow and common flow on cavitation. Magnitude of shock pressure was investigated at low cavitation number. Abstract: In a nuclear power plant, chalk river unidentified deposit (CRUD) is known as a deposit that is composed of corrosion and oxidation materials. It has a porous structure, which combines with boron that is injected into the coolant for controlling power levels. The buildup of corrosion products on the fuel cladding surface has proven to be particularly significant for both BWRs and PWRs. The high temperature of the cladding surface attracts impurities and chemical additives in the reactor coolant that deposit on the fuel rod surface in a process. The deposits on a fuel rod, known as CRUD, can be tenacious, insulative compounds capable of increasing the local clad temperature and accelerating clad corrosion—sometimes to the point of fuel failure. The deposition of CRUD on fuel cladding surfaces causes uneven heating of the reactor core. The situation is exacerbated by boron, which is added to the coolant to control power levels. However, boron becomes concentrated and is deposited within thick CRUD deposits. Ultrasonic mechanisms were developed but they have limitations for decontamination. In this experiment, a decontamination test was conducted using a sample sheet that was composed of SiC/water nanofluids. In addition, it was exposed to swirl flow and common flow for checking enhanced cavitation. It is measured by a pressure film, as shock pressure is associated with cavitation number. As a pressure film is wetted easily in water, it was injected into a holder. In the experiment, the maximum shock pressure was obtained during swirl flow at a low cavitation number. This indicates that pressure was concentrated on the pressure film. Consequently, cavitation can get rid of CRUD layers partially.